Desempeño profesional pedagógico del tutor de la especialidad de Medicina General Integral. - Prieto Peña, Ana Iris; González Sánchez, Anabel; Díaz Díaz, Alejandro Antuán; García Prieto, Harold (MEDISAN, 2025)
Introduction: To value the quality in the specialized training is necessary to evaluate the tutor's pedagogic professional performance. Objective: To contribute in the improvement of the pedagogic professional performance of the tutor in Comprehensive General Medicine specialty, from the beginning of the permanent and continuous training in the sciences of Medical Education. Method: A quasi-experiment study with pre-experiment design of a single pre test and post test group was carried out from September 2022 to September 2023. The study population was constituted by 20 tutors of 2 polyclinics from Colon municipality. The analyzed variable was the pedagogic professional performance of the tutor in the Comprehensive General Medicine specialty. An instrument was applied validated to the effect and 6 courses of professional training related to the identified learning necessities were developed. Results: Seven problems were identified. The indicators that showed significant changes were: knowledge of the education at work modalities in primary health care; knowledge on didactics in the tutorship; level in which tutorship activities are planned, implemented and controlled (75 % each one); degree of participation in activities of professional training related to the tutorship process (80 %). The problems that persisted were: knowledge about methodology of investigation and searching of scientific information (50 %); as well as publications and participation in events (60 %), reason why the elaboration of a training program was a suggestion. Conclusions: The evaluation feedback contributed to the improvement of the tutor´s pedagogic professional performance in the specialty of Comprehensive General Medicine in Colon municipality.